PENGATURAN TINDAK PIDANA CYBERSTALKING DALAM UU NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Windu Natalia, Siska; Atmadja, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
The development of science and technology especially computer and internet has brought a major effect to the life of human being, either in the positive side or in the negative side. The one of negative effect was increased crimes that used computer and internet, that called cyber crime. The most disturbing cyber crime which is still developing rapidly is the crime that related to the privacy of a human being, called cyberstalking. This kind of cyberstalking consists of harassing and threatening, but in the Act Number 11 of 2008 on Information and Electronic Transaction only regulates the act of threatening, while harassing hasn’t been clearly codified. Keywords: cyberstalking, harassing, threatening, Act Number 11 of 2008 on Information and Electronic Transaction.
Keywords: ITE, cyber crime